1969
DOI: 10.1139/v69-766
|View full text |Cite
|
Sign up to set email alerts
|

Salting-in and salting-out of polar nonelectrolytes

Abstract: The solubility of toluene and benzaldehyde was measured in NaBr and (11-Pr),NBr aqueous solutions at 25 "C, and the solubility of benzoic acid and nitrobenzene was measured in the same systems at 10,25, and 40 "C. The apparent molal volumes of the four nonelectrolytes were also determined from the densities of the saturated aqueous solutions.The volumes of mixing of the nonelectrolytes in water are all negative but become less so as their polarity increases. With the exception of benzoic acid, the salting-out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 9 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…The data points in the yellow shaded areas correspond to systems for which COSMOTherm and experiments disagree on the sign of K S . Experimental data from Almeida et al, 11 Desnoyers et al, 12 Endo et al, 7 Kampf et al, 9 Waxman et al 8 and Weng-Hui et al 13 (and references therein). Computed values for glyoxal and methylglyoxal correspond to the dihydrates, as these are likely to be the dominant form in aqueous solutions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The data points in the yellow shaded areas correspond to systems for which COSMOTherm and experiments disagree on the sign of K S . Experimental data from Almeida et al, 11 Desnoyers et al, 12 Endo et al, 7 Kampf et al, 9 Waxman et al 8 and Weng-Hui et al 13 (and references therein). Computed values for glyoxal and methylglyoxal correspond to the dihydrates, as these are likely to be the dominant form in aqueous solutions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(7) A calculation of the apparent molar volume in a saturated solution from our measurements by using the reported solubility (7) m 2 = 2.768 · 10 −2 mol · kg −1 and the extrapolated value of the solution density {equation (1) with parameters from table 2} resulted in 98.85 cm 3 · mol −1 , a value higher by 0.08 cm 3 · mol −1 . If the uncertainty of the apparent molar volume is assumed to be similar to that of the limiting partial molar volume (table 2) it may be concluded that the two values are in very good agreement.…”
Section: Partial Molar Volumesmentioning
confidence: 86%
“…For NAFA concentrations between 0.1 and 1 g L À1 , surface tension for a given NAFA concentration tends to decrease with increasing NaCl concentration due to salting out of NAFA by NaCl. [31][32][33][34][35][36][37][38] This trend is however not uniform over the whole composition range. In particular for surface tensions at t ¼ 0 s, a trough appears in the tting surface, possibly due to the sensitivity of the t to data points.…”
Section: Modelingmentioning
confidence: 88%